The efficacy of commercial decontamination agents differs between standardised test settings and research laboratory usage for a variety of bacterial species - Uy, Benedict; Read, Hannah; van de Pas, Shara; Marnane, Rebecca; Casu, Francesca; Swift, Simon; Wiles, Siouxsie (PeerJ, 2022)
Decontamination of surfaces and items plays an important role in reducing the spread of infectious microorganisms in many settings including hospitals and research institutes. Regardless of the location, appropriate decontamination procedures are required for maintaining biosafety and biosecurity. For example, effective decontamination of microbial cultures is essential to ensure proper biocontainment and safety within microbiological laboratories. To this end, many commercial decontamination agents are available which have been tested to a prescribed standard to substantiate their efficacy. However, these standardised tests are unlikely to accurately reflect many conditions encountered in medical and biomedical research. Despite this, laboratory workers and other users of decontamination agents may assume that all decontamination agents will work in all situations. We tested commonly used commercial decontamination agents against a range of bacterial species to determine their efficacy under real-world research laboratory conditions. As each decontamination agent has a different recommended dilution for use, to compare their efficacy we calculated their ‘effective ratio’ which reflects the difference between the manufacturer-recommended dilution and the dilution needed to achieve decontamination under real-world research laboratory conditions. Effective ratios above one indicate that the agent was effective at a dilution more dilute than recommended whereas effective ratios lower than one indicate that the agent required a higher concentration than recommended. Our results show that the quaternary ammonium agents TriGene Advance and Chemgene HLD4L were the most effective out of the agents tested, with biocidal activity measured at up to 64 times the recommended dilution. In contrast, hypochlorite (bleach) and Prevail™ (stabilised hydrogen peroxide) had the lowest effective ratios amongst the tested agents. In conclusion, our data suggests that not all decontamination agents will work at the recommended dilutions under real-world research laboratory conditions. We recommend that the protocols for the use of decontamination agents are verified under the specific conditions required to ensure they are fit for purpose.
Keywords: Escherichia coli; Staphylococcus aureus; Mycobacterium tuberculosis; Disinfection; Mycobacteria; Bleach; Trigene; Pseudomonas aeruginosa; Disinfecting agents; Bacillus